Investigating Scottish Long COVID community rehabilitation service models from the perspectives of people living with Long COVID and healthcare professionals: a qualitative descriptive study - Kay Cooper; Jenny Preston; Edward Duncan; Julie Cowie; Joanna Shim; Rachel Moss; Lyndsay Alexander; Jane Ormerod; Jacqui H Morris; Alison Love; Emma Stage; Tricia Tooman (BMJ Open, 2023)
Objectives This study aimed to explore the perceptions and experiences of barriers and facilitators to accessing Long COVID community rehabilitation.Design We used a qualitative descriptive design over two rounds of data collection with three participant groups: (1) people with experience of rehabilitation for Long COVID (PwLC); (2) National Health Service (NHS) staff delivering and/or managing community rehabilitation services (allied health professionals (AHPs)) and (3) NHS staff involved in strategic planning around Long COVID in their health board (Long COVID leads).Setting Four NHS Scotland territorial health boards.Participants 51 interviews: eight Long COVID leads (11 interviews); 15 AHPs (25 interviews) and 15 PwLC (15 interviews).Results Three key themes were identified: (1) accessing care for PwLC, (2) understanding Long COVID and its management and (3) strengths and limitations of existing Long COVID rehabilitation services.Conclusions Organisational delivery of Long COVID community rehabilitation is complex and presents multiple challenges. In addition, access to Long COVID community rehabilitation can be challenging. When accessed, these services are valued by PwLC but require adequate planning, publicity and resource. The findings presented here can be used by those developing and delivering services for people with Long COVID.